2007
DOI: 10.1177/019874290703200202
|View full text |Cite
|
Sign up to set email alerts
|

Professional Development for Teachers of Students with ADHD and Characteristics of ADHD

Abstract: Inservice education has the potential to provide teachers with knowledge and skills that are necessary to manage challenging classroom behavior and improve academic and social/emotional outcomes. To assess the effectiveness of 3 inservice programs that focused on knowledge, understanding, and/or functional-assessment interventions, we identified 49 educators of students with attention deficit-hyperactivity disorder (ADHD) and 196 of their students. Three months after implementing all programs we found improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 33 publications
1
21
0
9
Order By: Relevance
“…This finding is consistent with a growing body of experimental research that has shown that providing general education teachers with specialized training (e.g., professional development sessions) related to supporting students with behavior problems increases their use of effective instructional and/or behavior management approaches (Miranda et al 2002;Murray et al 2008;Owens et al 2005;Zentall and Javorsky 2007).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This finding is consistent with a growing body of experimental research that has shown that providing general education teachers with specialized training (e.g., professional development sessions) related to supporting students with behavior problems increases their use of effective instructional and/or behavior management approaches (Miranda et al 2002;Murray et al 2008;Owens et al 2005;Zentall and Javorsky 2007).…”
Section: Discussionsupporting
confidence: 87%
“…This latter finding suggests that providing general education teachers with training in how to work effectively with students with ADHD may increase their use of recommended behavior management approaches and instructional supports and strategies. Further experimental work is needed to confirm this hypothesis (e.g., Zentall and Javorsky 2007). Very few of the general education teachers surveyed in the present study had received moderate or extensive preservice or in-service training in ADHD.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Ces résultats vont dans le même sens que plusieurs études qui montrent que les activités ponctuelles de développe-ment professionnel des enseignants portant sur la gestion des comportements difficiles en classe produisent certains effets positifs à court terme, mais qu'elles semblent insuffisantes pour instaurer des changements à long terme dans les attitudes et les pratiques des enseignants (Arcia, Frank, Sánchez-LaCay et Fernández, 2000;Giallo et Hayes, 2007;Zentall et Javorsky, 2007) et qu'un soutien est nécessaire pour produire des changements (Sawka, McCurdy et Mannella, 2002). Selon Rousseau et ses collègues (Rousseau, Massé, Bergeron, Carignan et Lanaris, 2013), « il ne suffit pas de dire aux enseignants "quoi faire", mais bien de leur offrir des activités, des outils et du soutien pour qu'ils puissent réfléchir à leurs pratiques et aux façons d'exploiter leurs nouveaux savoirs dans leur contexte spécifique » et de les adapter aux besoins particuliers des élèves.…”
Section: Discussionunclassified